Personal growth initiative, self-efficacy and social support as predictors of life satisfaction among undergraduate students in Malaysia - Chow, Wen Chung; Diu, Jia Suan; Tneh, Sin Lin (2023)
University students experience major changes during the transition from secondary to university life thus it is crucial to investigate the contributing factors of undergraduate students’ life satisfaction. This study aimed to look into the relationships and predictive effects of personal growth initiatives, self-efficacy and social support on life satisfaction among undergraduate students in Malaysia. A non-probability sampling method which is the purposive sampling method was applied. A total sample of 176 undergraduate students was recruited in the study but only 140 samples were used in data analysis after the data cleaning. The results also show that there are significant and positive relationship between personal growth initiatives, self-efficacy and social support with life satisfaction among undergraduate students in Malaysia. Also, the linear regression results showed that personal growth initiative, self-efficacy and social support significantly predict the life satisfaction of undergraduate students in Malaysia. Therefore, it can be said that all six hypotheses have been supported in this study. In conclusion, this study gains a more profound comprehension of the importance of personal growth initiatives, self-efficacy and social support on life satisfaction among undergraduate students in Malaysia, which is crucial for formulating effective intervention initiatives that provide the necessary personal and social resources to increase the life satisfaction of the undergraduate students during their university period.